Structural basis for the stereospecific inhibition of the dual proline/hydroxyproline catabolic enzyme ALDH4A1 by trans‐4‐hydroxy‐L‐proline. (4th June 2021) - Bogner, Alexandra N.; Stiers, Kyle M.; McKay, Cole M.; Becker, Donald F.; Tanner, John J.
Abstract: Aldehyde dehydrogenase 4A1 (ALDH4A1) catalyzes the final steps of both proline and hydroxyproline catabolism. It is a dual substrate enzyme that catalyzes the NAD + ‐dependent oxidations of L‐glutamate‐γ‐semialdehyde to L‐glutamate (proline metabolism), and 4‐hydroxy‐L‐glutamate‐γ‐semialdehyde to 4‐erythro‐hydroxy‐L‐glutamate (hydroxyproline metabolism). Here we investigated the inhibition of mouse ALDH4A1 by the six stereoisomers of proline and 4‐hydroxyproline using steady‐state kinetics and X‐ray crystallography. Trans‐4‐hydroxy‐L‐proline is the strongest of the inhibitors studied, characterized by a competitive inhibition constant of 0.7 mM, followed by L‐proline (1.9 mM). The other compounds are very weak inhibitors (approximately 10 mM or greater). Insight into the selectivity for L‐stereoisomers was obtained by solving crystal structures of ALDH4A1 complexed with trans‐4‐hydroxy‐L‐proline and trans‐4‐hydroxy‐D‐proline. The structures suggest that the 10‐fold greater preference for the L‐stereoisomer is due to a serine residue that hydrogen bonds to the amine group of trans‐4‐hydroxy‐L‐proline. In contrast, the amine group of the D‐stereoisomer lacks a direct interaction with the enzyme due to a different orientation of the pyrrolidine ring. These results suggest that hydroxyproline catabolism is subject to substrate inhibition by trans‐4‐hydroxy‐L‐proline, analogous to the known inhibition of proline catabolism by L‐proline. Also, drugs targeting the first enzyme of hydroxyproline catabolism, by elevating the level of trans‐4‐hydroxy‐L‐proline, may inadvertently impair proline catabolism by the inhibition of ALDH4A1. Abstract : PDB Code(s): 7MER and 7MES ;